The influence of different genres of music on the performance of medical students on standardized laparoscopic exercises - Nees, Lisa Katharina; Grozinger, Philipp; Orthmann, Natalie; Rippinger, Nathalie; Hennigs, André; Sohn, Christof; Domschke, Christoph; Wallwiener, Markus; Rom, Joachim; Riedel, Fabian (Journal of surgical education, 2021)
Purpose - Whether and how music influences the performance of surgical procedures such as laparoscopy is unclear and can be feasibly determined using laparoscopic box training tools under standardized conditions. The aim of this prospective study is to evaluate the effect of different genres of music on the performance of laparoscopic novices. - Methods - Between May 2018 and December 2018, n=82 students (38 male, 44 female) from Heidelberg University Medical School performed 3 different laparoscopic exercises (A, B, C) from the “Luebecker Toolbox” with 2 repetitions each under standardized conditions. Time was recorded for each exercise. The students were assigned either to one of four groups, each of which was exposed to a compilation of music from 1 genre (hip hop, classical, rock, or mixed radio music), or to a fifth, control group, without exposure to music. The music was played at a constant sound pressure level of 70 decibels . Each group was compared with the others using a t-test for independent samples. - Results - Exposure to music generally led to better performance compared with the control group. Compared with exposure to mixed radio music or to rock, significantly better performance could be demonstrated for exposure to classical music in Exercise B, with an average exposure time of 127 s needed (± 21.4; p < 0.05). No significant differences could be demonstrated for Exercise A, though for classical music, best performance was possible with 120 s (±17.3) of exposure. In Exercise C, hip hop triggered significantly better performance than rock or radio music (p < 0.05). - Conclusions - At an sound pressure level of 70 decibels, exposure to classical music or hip hop appears to have beneficial effects on training performance for surgical novices under standardized conditions.